La construcción ciudadana como nueva forma de poder (interrelación social) con énfasis holístico para las comunidades - Mieles Velásquez, David (2014)
Civic development as a new ruling power (social interrelation) with a holistic emphasis for communities has become a real means of civic participation. By developing a true sense of citizenship among the inhabitants of the communities, transmitting and explaining the rights and obligations they as citizens are called to demand and fulfill, a community empowerment is fomented to help them take the most important decisions on their benefit or detriment.